Promoting research culture among politechnic’s hospitality students - Zakaria, Mohd. Amin; Mohd. Noor, Norani (2008)
This small-scale study is grounded on empirical qualitative data deriving from purposive sampling of 10 diploma students in hospitality management course of Politeknik Johor Bahru. It is argued that there is a lack of research culture in diploma students. Since there is no research-based module in the 3-year program, these graduates will not be able to use their thinking ability at the maximum. We emphasize the importance of creating a research culture in thinking and learning while in junior college (diploma) to enable students to adapt to the university learning environment in the future. The data collected from the surveys and interview will be calculated using mode and (f) frequency of score. Student’s research activities have become significance of promoting thinking and learning process especially in exploring new things, get feedback on what they have done, improving skills and creativity and finally, in constructing the appropriate decision making. Further, it has also been discussed on how such skills and dispositions are becoming an imperative significant on survival and growth towards student’s future life. Some suggestions on the infrastructure and curriculum of the college are made. It is also to look carefully at the neediness of research committees and research unit which are the central of the organization tools for research development, by analysing and describing the range of research culture in the college: from absence to optimal. The paper will hopefully contribute to the basic theoretical and as an applied framework that may support the further development of research culture in the college